The influence of pre-season training loads on in-season match activities in professional Australian football players - Johnston, R. D.; Murray, N. B.; Austin, D. J. (Science and Medicine in Football, 2019)
Objectives: To determine the impact of pre-season training loads on in-season match activity profiles in professional Australian football (AF) players. Methods: Forty-four professional AF players participated in this study. Sixty-nine pre-season training and in-season match profiles were monitored using global positioning system (GPS) microtechnology and technical statistics across two seasons. Technical performance was measured as the Player Rank score provided by Champion Data. Players were divided into three equal training load groups based on total distance accumulated during pre-season. Results: Players in the high training load (HTL) group performed more relative total and high-speed distance in matches compared with the moderate (MTL; ES = 0.73-0.86) and low (LTL; ES = 0.68-1.31) training load groups, with the differences becoming greater as the season progressed. There were no clear differences in Player Rank score between groups. There were positive relationships between pre-season high-speed running and match relative distance (p = 0.001; r = 0.417; r2 = 0.174) and match relative high-speed running (p = 0.001; r = 0.561; r2 = 0.314), which were greatest in the HTL group. Conclusions: High pre-season training loads are associated with increased physical match activities, but do not appear to impact technical performance.